Prevalence of hospital admissions due to diabetes mellitus in Brazil between 2020 and 2023 - Jacomini , Cínthia Pereira; Palason, Larissa; Marino, Lilian Duarte Granado Ferreira; Rodrigues , Ana Carolina Rasia de Mello; Emerick, Ana Clara Assis Alves; Jacomini, Renata Pereira (Seven Editora, 2023)
Diabetes mellitus (DM) is characterized as a non-transmissible chronic disease and is considered a public health problem for all countries, regardless of their degree of development. The evolution of DM results in macrovascular complications such as systemic arterial heart disease, stroke, peripheral arterial disease, and microvascular causes such as retinopathy, nephropathy, and neuropathy. This is a descriptive, ecological, and quantitative study on hospitalization for diabetes mellitus from January 2020 to May 2023 (last month with data available in the system at the time of consultation). Data regarding hospitalizations, deaths, gender (male and female), age group, average length of stay and hospital costs were collected from the Hospital Information System of the Unified Health System (SIH/SUS). The tabulation and descriptive analysis of the data were inserted in the Microsoft Office Excel program. There were 445,416 hospital admissions and 19,998 deaths from DM. In addition, hospital costs above 351 million and an average hospital stay of 7.12 days stood out. It was found that information on the number of hospitalizations, hospital costs and deaths is suffering a significant increase every year because of complications from DM, causing significant impacts on public coffers. DOI:https://doi.org/10.56238/sevened2023.006-070